From genes to landscapes: Pattern formation and self‐regulation in raised bogs with an example from Tierra del Fuego. Issue 4 (4th April 2022) - Couwenberg, John; Baumann, Martin; Lamkowski, Paul; Joosten, Hans
Abstract: We studied a pristine, prominently patterned raised bog in Tierra del Fuego, Argentina, to disentangle the complex interactions among plants and water and peat. The studied bog lacks complicating features often posed by other bogs. It is completely dominated by Sphagnum magellanicum, which covers all niches and growth forms, and is joined by only a dozen higher plant species; it is entirely ombrotrophic with very sharp borders to the surrounding fen; it has only one type of peat that shows an only limited range in degree of decomposition; and it is situated in a very even climate with minimal differences in rainfall and temperature over the year. We present detailed measurements along a 498‐m‐long transect crossing the bog, including water table measurements ( n  = 498), contiguous vegetation relevés ( n  = 248), hydraulic conductivity just below the water table ( n  = 246), and hydraulic conductivity in 11 depth profiles ( n  = 291); degree of humification of the corresponding peat was assessed in conjunction with the hydraulic conductivity measurements ( n  = 537). Sphagnum magellanicum moss samples were collected every 2 m along this transect as well and genotyped ( n  = 242). In addition, along short, 26‐m‐long transects crossing strings and flarks water table and hydraulic conductivity just below the water table were measured every meter. Sphagnum growth forms were assessed, and the vegetation of the entire bog was mapped in 10 × 10‐m relevés ( n  = 3322). A simulation model was applied to a generalized shape of the bog and produced surface patterns that well matched those seen in the field. The results were integrated with information from the literature and discussed in the framework of a self‐regulating and self‐organizing raised bog. We identified 19 hydrological feedback mechanisms. We found that the various mechanisms overlap in both space and time, which means there is redundancy in the self‐regulation of the system. Raised bogs, when in a natural state, are among the most resilient ecosystems known; resilience that is provided by feedbacks and backup systems to these feedbacks.